ijps 2020
DOI: 10.36468/pharmaceutical-sciences.632
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PEGylated Liposomal Ginsenoside;Formulation Design and in vitro Evaluation

Abstract: Cui et al.: Ginsenoside Rg3-loaded PEGylated liposomesIn this study, ginsenoside Rg3-loaded PEGylated liposomes were prepared and optimized using the Box-Behnken design. These liposomes were characterized, the cumulative release profiles were investigated and compared with ginsenoside Rg 3 -loaded liposomes in vitro. To improve the stability ginsenoside Rg3-loaded PEGylated liposomes were freeze-dried and the lyoprotectants to be added were screened. The results showed that the liposomes have a small particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Growth rate of BALB/c nude mice inoculated with A549 tumor cells was significantly inhibited by L-Rg3. Besides, Tumor growth can be inhibited by liposome by reducing MVD and enhancing angiogenesis inhibition [ 97 ] DSPE-PEG2000 Rg3 NA NA 7.44% ± 0.08% 85.24% ± 1.02% In vitro : Rg3-PEGylated liposomes showed sustained release [ 96 ] DSPE-PEG2000 Rh2 NA A549 cells/mice 15.3% 88.2% In vitro : IC 50 values of A549 cells treated with DLT indicated that tumor growth could be inhibited by DLT In vivo : DLT showed stronger antiproliferation and apoptosis effects on xenografted tumors. DDS was safer than cisplatin in treatment of tumors [ 98 ] mPEG-PLA Rh2 Passive tumor targeting HepG2/mice NA 94.93% ± 4.18% In vivo : Fluorescence intensity at tumor site decreased gradually after injection of PLP for 8 h and lasted for 24 h. Rh2-PLP was superior to Rh2-LP and Rh2-CLP in anti-tumor effect [ 100 ] EYPC/Rh2 /Rg3/Rg5 PTX/Rh2/Rg3 /Rg5 Active targeting: Rh2/Rg3/Rg5 BGC-823 cells/mice Rh2: 5.6% ± 0.3% Rg3: 7.3% ± 0.4% Rg5: 4% ± 0.1% Rh2: 91.3% ± 2.1% Rg3: 95.5% ± 3.3% Rg5: 82.8% ± 1.6% In vitro : Ginsenoside liposome can be accumulated in tumor for recognizing GLUT carrier on tumor cell membrane In vivo : Ginsenosides showed significant synergistic effects with PTX for antitumor activity [ 26 ] EYPC/Rh2 PTX/Rh2 Active targeting: Rh2 4T1 cells /mice 5.6% …”
Section: Ginsenosides As Bifunctional Drugs and Nanocarriers In Ddssmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth rate of BALB/c nude mice inoculated with A549 tumor cells was significantly inhibited by L-Rg3. Besides, Tumor growth can be inhibited by liposome by reducing MVD and enhancing angiogenesis inhibition [ 97 ] DSPE-PEG2000 Rg3 NA NA 7.44% ± 0.08% 85.24% ± 1.02% In vitro : Rg3-PEGylated liposomes showed sustained release [ 96 ] DSPE-PEG2000 Rh2 NA A549 cells/mice 15.3% 88.2% In vitro : IC 50 values of A549 cells treated with DLT indicated that tumor growth could be inhibited by DLT In vivo : DLT showed stronger antiproliferation and apoptosis effects on xenografted tumors. DDS was safer than cisplatin in treatment of tumors [ 98 ] mPEG-PLA Rh2 Passive tumor targeting HepG2/mice NA 94.93% ± 4.18% In vivo : Fluorescence intensity at tumor site decreased gradually after injection of PLP for 8 h and lasted for 24 h. Rh2-PLP was superior to Rh2-LP and Rh2-CLP in anti-tumor effect [ 100 ] EYPC/Rh2 /Rg3/Rg5 PTX/Rh2/Rg3 /Rg5 Active targeting: Rh2/Rg3/Rg5 BGC-823 cells/mice Rh2: 5.6% ± 0.3% Rg3: 7.3% ± 0.4% Rg5: 4% ± 0.1% Rh2: 91.3% ± 2.1% Rg3: 95.5% ± 3.3% Rg5: 82.8% ± 1.6% In vitro : Ginsenoside liposome can be accumulated in tumor for recognizing GLUT carrier on tumor cell membrane In vivo : Ginsenosides showed significant synergistic effects with PTX for antitumor activity [ 26 ] EYPC/Rh2 PTX/Rh2 Active targeting: Rh2 4T1 cells /mice 5.6% …”
Section: Ginsenosides As Bifunctional Drugs and Nanocarriers In Ddssmentioning
confidence: 99%
“…It has been demonstrated that PEGylated liposomes loading ginsenoside Rg3 display sustained-release and enhanced therapeutic effects with longer blood circulation time and enhanced drug uptake [ 96 , 97 ]. In particular, the growth rate of BALB/c nude mice inoculated with A549 tumor cells was inhibited significantly by L-Rg3 after intravenous injection of the drug, which subdued the tumor growth through reducing microvessel density (MVD) and enhancing angiogenesis inhibition [ 97 ].…”
Section: Ginsenosides As Bifunctional Drugs and Nanocarriers In Ddssmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The most applied stratagem to overcome the solubility issue is encapsulation, which can improve oral bioavailability, significantly prolong pharmacodynamics and reduce drug toxicity. 25,[28][29][30] The wall material for the encapsulation could be polymer, 29,[31][32][33] or small molecules like cholesterol accompanied with polyethylene glycol (PEG), that has been questioned due to various disadvantages, 31 while the popular capsules could be liposomes, 5,31,[34][35][36] gel 37 and micelle. 38,39 In our early work, nano-vesicles of conjugated linoleic acid (CLA) were prepared with different surfactants and widened pH window of vesiculation.…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical application is limited due to its poor water solubility, short circulating half‐life and poor specificity for tumor tissue targeting 27 . The most applied stratagem to overcome the solubility issue is encapsulation, which can improve oral bioavailability, significantly prolong pharmacodynamics and reduce drug toxicity 25,28‐30 . The wall material for the encapsulation could be polymer, 29,31‐33 or small molecules like cholesterol accompanied with polyethylene glycol (PEG), that has been questioned due to various disadvantages, 31 while the popular capsules could be liposomes, 5,31,34‐36 gel 37 and micelle 38,39 …”
Section: Introductionmentioning
confidence: 99%